DEVELOPMENT OF E-HANDOUTS ACID-BASE MATERIALS IN HIGH SCHOOL USING THE SOROGAN LEARNING METHOD - M. Zaki Ghufron; Rinaningsih Rinaningsih (Universitas Negeri Surabaya, 2026)
The Independent Curriculum encourages educators to create innovative, interactive, and student-centered learning processes, especially in chemistry lessons that contain many abstract concepts that often cause difficulties in understanding the material. One alternative that can be implemented is the development of e-handouts combined with the sorogan learning method so that students are more active and able to learn independently in understanding the learning material. This study aims to develop e-handouts on acid-base material using the sorogan learning method and to determine the level of validity, practicality, and effectiveness in improving student mastery of concepts. The method used in this study is Research and Development (R&D) which includes a preliminary study stage, media development, and limited trials with 28 high school students as research subjects. The research instruments consisted of validation sheets, student activity observation sheets, student response questionnaires, and pretests and posttests. The results showed that the developed e-handouts met the validity criteria based on content validity with mode 5 categorized as very valid and construct validity with mode 4 categorized as valid. The developed learning media is also considered practical based on the results of observations of student activities at 89% and student response questionnaires at 81%. In addition, the e-handout was declared effective in improving student conceptual mastery based on the N-Gain Score results with a medium category of 61% and a high category of 4%. Thus, the e-handout based on the sorogan learning method is able to help students understand acid-base concepts more independently, actively, and comprehensively. This research contributes to the development of digital-based chemistry learning media that can be used as an alternative innovative teaching material to support the implementation of the Independent Curriculum through more individualized, interactive, and effective learning.